Higher Education Initiatives for Disaster and Emergency Health in Iran - Ali Ardalan; Alireza Mesdaghinia; Gholamreza Masoumi; Kourosh Holakouie Naieni; Elham Ahmadnezhad (Tehran University of Medical Sciences, 2013)
Iran's health system is expanding the disaster and emergency higher education programs over the country to enhance the capacity of human resources for effective and efficient disaster mitigation, preparedness, response and recovery. In this article we present an overview about the initiatives and progress of disaster and emergency health higher education in Iran. Following the Bam earthquake, in collaboration with the Ministry of Health & Medical Education and National Institute of Health Research, School of Public Health at the Tehran University of Medical Sciences, Iran took the initiative to develop a Master of Public Health (MPH) with disaster concentration in 2006, a PhD in disaster and emergency health in 2011, and a well constructed certificate course in 2008 entitled Disaster Health Management and Risk Reduction (DHMR). Iran, Kerman and Shahid Beheshti Universities of Medical Sciences and University of Social Welfare and Rehabilitation are other academia that joined this initiative. Regarding the importance of programs evaluation, we have planned for a comprehensive evaluation of MPH and DHMR programs in 2013-4 and the Accreditation and Evaluation Board of Disaster & Emergency Health, based in MOH&ME, is responsible for evaluation of the PhD program in 3-5 years from initiation.